Socio-Demographic Determinants and Morbidity Profile of People Engaged in Bag Making Occupation in An Urban Slum of Mumbai, India - A Giri Purushottam; Pawan V Meshram; Abhiram M Kasbe (Medsci Publications, 2012)
Background: Bag making is a kind of occupation which comes under unorganized sector. An occupation is always associated with some risk which can account to health hazard. Bag makers are also not an exception to this rule. Objectives: A present study was conducted to assess the socio-demographic determinants and morbidity profile among bag makers. Material and methods: A cross-sectional study was carried out in the field practice area (cheetah camp urban health centre) of the T. N. Medical College, Mumbai during the period of March 2008 to August 2009. A total 800 bag makers from cheetah camp area were interviewed and examined. A pre-tested interview tool was used to collect necessary information such as clinical history, socio-demographic profile, clinical examination findings and investigations performed. Results were analysed using Statistical Package of Social Sciences (SPSS) version -17.0. Results: In the present study, out of the 800 study participants taken in to consideration, 95.9% were males and 4.1% were females. Musculoskeletal problems were most predominant, seen in 76.3% participants followed by skin problems (40.9%), while 30.3% participants presented with gastrointestinal and 17.3% with respiratory ailment. Thirty three percent workers had ocular morbidity and injuries were observed in 26.3% workers including minor injuries such as cuts and abrasions. Conclusion: In this study, large proportion of workers suffered from work related symptomatic morbidities mainly of musculoskeletal problems, followed by skin, eye, gastrointestinal and respiratory problems. Bag makers should be educated regarding their work related health hazards so that they are detected at the earliest and proper treatment can be initiated.